2015
DOI: 10.1002/pen.24167
|View full text |Cite
|
Sign up to set email alerts
|

DMA testing of epoxy resins: The importance of dimensions

Abstract: Dynamic mechanical analysis is commonly used to characterize thermoset polymers at temperatures ranging from well below to well above their glass transition temperatures. Many sample fixtures are available; however, the best clamp and best sample dimensions for a given material are not often readily apparent. Five different epoxy amine networks with glass transitions spanning over 1008C were characterized on three-point bending, dual cantilever, and single cantilever clamps with both constant thickness and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 90 publications
(153 reference statements)
2
70
0
Order By: Relevance
“…MW c data were calculated using the minimum value of the storage modulus for the thick samples using the theory of rubber elasticity (Equation ) where ρ is the cured resin density, R is the gas constant, T E ′min is the temperature at which the storage modulus is minimized, and E ′ min is the minimum value of the storage modulus. Only the thick samples were stiff enough to ensure reliable modulus data in the rubbery regime MWnormalc=3ρRTEminEmin…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MW c data were calculated using the minimum value of the storage modulus for the thick samples using the theory of rubber elasticity (Equation ) where ρ is the cured resin density, R is the gas constant, T E ′min is the temperature at which the storage modulus is minimized, and E ′ min is the minimum value of the storage modulus. Only the thick samples were stiff enough to ensure reliable modulus data in the rubbery regime MWnormalc=3ρRTEminEmin…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the thermomechanical properties and thermal stability exhibited by the cured resins produced in this study were similar to comparable thermosets reported in literature, but consisted of much greater bio‐based content. In particular, these bio‐based polymers had properties higher than that of EPON828‐Jeffamine systems, while lower than that of EPON828‐PACM . This bioderivation alone makes these tunable‐property thermosets of immediate and significant value as replacements for less‐sustainably sourced and more hazardous incumbent resins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were tested at 1 Hz and amplitude of 2.5 µm, while subjected to a temperature ramp from −20 to 200 °C at a rate of 2 °C/min. DMA can be used to determine the glass transition temperature of a polymer through three methods . Storage modulus ( E ′) is one method where the inflection point is considered the T g .…”
Section: Methodsmentioning
confidence: 99%